1986
DOI: 10.3382/ps.0650726
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Age of Bird and Season of the Year on Egg Quality. II. Haugh Units and Compositional Attributes

Abstract: Eggs were obtained from eight commercial egg production houses over 12 months. The effects of age of bird and season of the year on Haugh units and egg composition were analyzed. Haugh units decreased significantly and egg weight increased significantly as age of bird increased. No seasonal effects on either Haugh units or egg weight were observed. Yolk weight and percentage of yolk increased significantly as the bird aged but were not significantly affected by season of the year. Albumen weight increased as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
1
2
0
1
Order By: Relevance
“…Several investigators reported similar season effects regarding yolk color (Simeon et al, 2018) specific gravity, shell weight per unit of egg surface area (Izat et al, 1985) and shell thickness (Islam et al, 2001;Moula et al, 2013). In contrast to our results, Izat et al, (1985) reported that shell density was higher in the winter, but some other investigators reported no significant season effect regarding the Haugh unit values, (Izat et al, 1986;Simeon et al, 2018) yolk color grades and yolk albumin ratio (Moula et al, 2013). These differences might be due to different strains, age of the birds, size of the egg, nutrition, heat stress and egg poor handling on farm and marketing channels.…”
Section: Effects Of Storage Period Marketing Channels and Season On Internal And External Quality Of Commercial Table Eggs Marketed In Risupporting
confidence: 57%
“…Several investigators reported similar season effects regarding yolk color (Simeon et al, 2018) specific gravity, shell weight per unit of egg surface area (Izat et al, 1985) and shell thickness (Islam et al, 2001;Moula et al, 2013). In contrast to our results, Izat et al, (1985) reported that shell density was higher in the winter, but some other investigators reported no significant season effect regarding the Haugh unit values, (Izat et al, 1986;Simeon et al, 2018) yolk color grades and yolk albumin ratio (Moula et al, 2013). These differences might be due to different strains, age of the birds, size of the egg, nutrition, heat stress and egg poor handling on farm and marketing channels.…”
Section: Effects Of Storage Period Marketing Channels and Season On Internal And External Quality Of Commercial Table Eggs Marketed In Risupporting
confidence: 57%
“…In agreement with a previous study ( Silversides and Scott, 2001 ), egg weight was observed to increase with age in the present experiment, and the higher weight ratio of yolk to white might contribute to this effect of aging on egg weight ( Ahn et al., 1997 ). In addition, probably due to the reduced albumen weight with increasing age ( Izat et al., 1986 ), a lower value of albumen height was observed in the aging birds from this study, which might in part account for the lower freshness of egg laid by the old birds. As for eggshell quality, the present study showed that eggs harvested from 525-d-old hens exhibited lower eggshell strength and thickness, implying the frangibility of eggshells from older laying hens.…”
Section: Discussionmentioning
confidence: 62%
“…Changing attitudes to human nutrition have found that as the age of hens increased, egg weight and percent yolk increased, whilst percent albumen decreased (Fletcher et al, 1981 andIzat et al, 1986).…”
Section: Introductionmentioning
confidence: 99%